TAMAN SATWA KEBON REJO DENGAN PENDEKATAN - Nanda Dhanendra; Titis Srimuda Pitana; Kusumaningdyah Nurul Handayani (ARSITEKTURA, 2016)
Taman Satwa Taru Jurug is now lost its luster. Lack of maintenance makes the public interest to visit Taman Satwa Taru Jurug gradually receding. “Kebon Rojo” was a garden of Kasunanan Surakarta Palace formerly reserved for the royal family recreation area. Kebon Rojo applied the concept of “olah raga” (physical activities), olah rasa (psychic management), and “olah-olah (culinary process) which belonged to the application of customary values of Java. The Kebon Rojo concept is a potential that can be used as the first step of planning and design concept considerations of Kebon Rojo wildlife park in Surakarta. The zoo or wildlife park is closely related to nature, especially animals and plants, the ecological aspects in it cannot be ruled out. Therefore, the output of the design concept that is considering the ecological aspect is also very necessary. The design problem is how to apply the principle of the former Kebon Rojo, which can also apply the concept of Eco-Cultural Architecture based on the concept of sustainable, which not only includes something that is seen as physical entity such as environment and nature, but also include something that is not seen as a physical entity, such as culture, habits and customs. In planing process, it is essential to collect particular data, especially about the history, location, and also technical requirements of wildlife park. The design result is, “Kebon Rojo” wildlife park Surakarta can be a public space which can be used as a recreational area with the concept of education and conservation, which become a home for a wide range of plants and animals, which apply the concept of Eco-Cultural Architecture by implementing the values and principles of “Kebon Rojo” royal family garden., Keywords: Wildlife Park, Ecology, Cultural, Eco-Cultural Architecture